MAGNETOCONTROLLABLE NON-STATIONARY ISOTHERMAL MASS TRANSFER IN MAGNETIC FLUIDS IN THE VICINITY OF FERRO- AND DIAMAGNETIC CONDENSATION CORES - Ivanov, A.S.; Khokhriakova (Bushueva), K.A.; Polezhaeva, E.A. (Perm Federal Research Centre Journal, 2016)
The paper reports about the study of non-stationary isothermal magneto-controllable convective flows in the vicinity of ferro- and diamagnetic bodies, immersed into magnetic fluids and playing the role of magnetic condensation cores. The cores are the sources of the inhomogeneous magnetic field, which causes a 1-st order phase transition of the «gas-liquid» type in magnetic fluids and the initiation of intensive inner flows driven by magnetophoresis of drop-like aggregates. When the applied magnetic field is removed, natural solutal convection takes place all over the volume of the fluid sample. The simulation of convective flows was made in the framework of three different theories of a first-order phase transition in magnetic fluids. The comparison between several simulations and physical experiment helps to choose the theory which fits the experimental data best.